Purification and properties of glutamate dehydrogenase from a thermophilic bacillus. - Epstein, I (1975)
A 250- to 300-fold purification of a nicotinamide adenine denucleotide phosphate (NADP)-dependent glutamate dehydrogenase (GDH, E.C. 1.4.1.4) with a yield of 60% from a thermophilic bacillus is described. More than one NADP-specific GDH was detected by polyacrylamide gel electrophoresis. The enzyme is of high molecular weight (approximately 2 X 10-6), similar to that of the beef and frog liver GDH. The pI of the thermophilic GDH is at pH 5.24. The enzyme is highly thermostable at the pH range of 5.8 to 9.0. The purified GDH, unlike the crude enzyme, was very labile at subzero temperatures. An unidentified factor(s) from the crude cell-free extract prevented the inactivation of the purified GDH at -70 C. Various reactants of the GDH system and D-glutamate also protected, to some extent, the enzyme from inactivation at -70 C. From the Michaelis constants for glutamate (1.1 X 10-2M), NADP (3 X 10-4M), ammonia (2.1 X 10-2M), alpha-ketoglutarate (1.3 X 10-3M), and reduced NADP (5.3 X 10-5M), it is suggested that the enzyme catalyzes in vivo the formation of glutamate from ammonia and alpha-ketoglutarate. The amination of alpha-ketoglutarate and deamination of glutamate by the thermophilic GDH are optimal at the pH values of 7.2 and 8.4, respectively.